2004
DOI: 10.2307/1543542
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable Defense: A Nudibranch Mucus Inhibits Nematocyst Discharge and Changes With Prey Type

Abstract: Nudibranchs that feed on cnidarians must defend themselves from the prey's nematocysts or risk their own injury or death. While a nudibranch's mucus has been thought to protect the animal from nematocyst discharge, an inhibition of discharge by nudibranch mucus has never been shown. The current study investigated whether mucus from the aeolid nudibranch Aeolidia papillosa would inhibit nematocyst discharge from four species of sea anemone prey. Sea anemone tentacles were contacted with mucus-coated gelatin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Due to the loss of shell during their evolution, sea slugs need sophisticated chemical defence mechanisms for survival; the toxins they possess are a wide choice (Gunthorpe and Cameron 1987;Greenwood et al 2004). They could be produced de novo or taken up via prey diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the loss of shell during their evolution, sea slugs need sophisticated chemical defence mechanisms for survival; the toxins they possess are a wide choice (Gunthorpe and Cameron 1987;Greenwood et al 2004). They could be produced de novo or taken up via prey diet.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the cnidocysts do not harm the predators. Greenwood et al (2004) observed that the mucus of Aeolidia papillosa inhibits the discharge of nematocysts from different species of sea anemones. A unique feature is the ability of nudibranchs to annex intact cnidarian nematocysts, transferring these unfired kleptocnides as chemical weapons into their dorsal cerata.…”
Section: Introductionmentioning
confidence: 99%
“…When the prey was changed to another anemone species, the nudibranch mucus also changed within 2 wk to inhibit the nematocyst discharge by the new prey species. Greenwood et al (2004) noted that sea anemones do not sting themselves or clone-mates and hypothesised that they may produce compounds which prevent nematocyst discharge that are yet to be identified. It is interesting to note that some of the most aggressive corals on Indo-Pacific reefs are among the most copious mucus producers.…”
Section: Defence Against Space Invasion By Other Coralsmentioning
confidence: 99%
“…It is clear that the exact nature of stimuli involved in competitive interactions between corals remains elusive. Recent work with nudibranch molluscs (Greenwood et al 2004) has shown that they are capable of producing mucus which inhibits nematocyst discharge from anemone prey. When the prey was changed to another anemone species, the nudibranch mucus also changed within 2 wk to inhibit the nematocyst discharge by the new prey species.…”
Section: Defence Against Space Invasion By Other Coralsmentioning
confidence: 99%
“…Mucus has also been recognized as an inhibitor of nematocyst discharge in sea anemone and clownfish interaction (Lubbock 1979) and in sea anemone and nudibranch interaction (Mauch and Elliott 1997;Greenwood et al 2004). Mucin, or a similar prey-produced molecule, could be used at one set of concentrations to act as a nematocystsensitizing agent, and, at higher concentrations, as an inhibitor, which might contribute to the feeding-satiety control mechanisms in hydra ( Thorington and Hessinger 1988;Scappaticci et al 2010).…”
Section: Proteinsmentioning
confidence: 99%